Matrix metalloproteinase (MMP)‐7 in Barrett's esophagus and esophageal adenocarcinoma: expression, metabolism, and functional significance. Issue 10 (20th May 2018) - Garalla, Hanan M.; Lertkowit, Nantaporn; Tiszlavicz, Laszlo; Reisz, Zita; Holmberg, Chris; Beynon, Rob; Simpson, Deborah; Varga, Akos; Kumar, Jothi Dinesh; Dodd, Steven; Pritchard, David Mark; Moore, Andrew R.; et al.
Abstract: Matrix metalloproteinase (MMP)‐7, unlike many MMPs, is typically expressed in epithelial cells. It has been linked to epithelial responses to infection, injury, and tissue remodeling including the progression of a number of cancers. We have now examined how MMP‐7 expression changes in the progression to esophageal adenocarcinoma (EAC), and have studied mechanisms regulating its expression and its functional significance. Immunohistochemistry revealed that MMP‐7 was weakly expressed in normal squamous epithelium adjacent to EAC but was abundant in epithelial cells in both preneoplastic lesions of Barrett's esophagus and EAC particularly at the invasive front. In the stroma, putative myofibroblasts expressing MMP‐7 were abundant at the invasive front but were scarce or absent in adjacent tissue. Western blot and ELISA revealed high constitutive secretion of proMMP‐7 in an EAC cell line (OE33) that was inhibited by the phosphatidylinositol (PI) 3‐kinase inhibitor LY294002 but not by inhibitors of protein kinase C, or MAP kinase activation. There was detectable proMMP‐7 in cultured esophageal myofibroblasts but it was undetectable in media. Possible metabolism of MMP‐7 by myofibroblasts studied by proteomic analysis indicated degradation via extensive endopeptidase, followed by amino‐ and carboxpeptidase, cleavages. Myofibroblasts exhibited increased migration and invasion in response to conditioned media from OE33 cells that was reduced by MMP‐7 knockdown and immunoneutralization. Thus, MMP‑7 expression increases at the invasive front in EAC which may be partly attributable to activation of PI 3‐kinase. Secreted MMP‐7 may modify the tumor microenvironment by stimulating stromal cell migration and invasion. Abstract : Matrix metalloproteinase (MMP)‐7 was increased in epithelial cells in preneoplastic lesions (Barrett's esophagus) and esophageal adenocarcinoma cells; in an EAC cell line (OE33) high expression of MMP‐7 was inhibited by the phosphatidylinositol (PI) 3‐kinase inhibitor LY294002. MMP‐7 increased the migration and invasion of esophageal stromal cells (myofibroblasts). Thus, secreted MMP‐7 may modify the esophageal tumor microenvironment by stimulating stromal cell migration and invasion.